Seleção de fungos filamentosos para produção de ácidos graxos poli-insaturados - Tonato, Denise (2015)
In this work, 150 fungal strains isolated in the Pampa biome were evaluated for. The microbial oil was produced by submerged fermentation in shaken flasks at 120 rpm, 28 °C for 7 days. The lipids were extracted from cells by Soxhlet (AOAC) method and the fatty acids profile determined by gas chromatography (GC-FID). Seven strains presented the best results in terms of lipids production, which were selected to evaluate the influence of temperature on microbial oil production and PUFA profiles. The fermentations were conducted under the same conditions previously defined at 15 and 28 °C. The fungus SPII65, identified as belonging to the genus Nigrospora sp., produced the highest level of lipids, yielding 11.28% and 6.02% with PUFAs production of 51.94% and 42.39% at 28 °C and 15 °C, respectively. From the results obtained, it was conceived a Plackett-Burmann design to investigate the main effects of temperature (15-25 °C), pH (4.0-6.0), agitation (120-200 rpm), corn steep liquor concentration (5-15% (v/v)) and sucrose (60-180 g/L). The largest production of PUFAs (55.75%) was observed in the smallest evaluated temperatures (15 °C), whereas the maximum lipid production was 5.54% at 25 °C. Lower lipid contents were produced using industrial medium compared to the results obtained with synthetic medium. PUFAs profiles were similar in the culture media evaluated.